p35_023 - − 4 df ) = 22 cm ± 1 2 p (44 cm) 2 − 4(44...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
23. Using Eq. 35-9 and noting that p + i = d =44cm ,weobtain p 2 dp + df = 0. Therefore, p = 1 2 ( d ± p d
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: − 4 df ) = 22 cm ± 1 2 p (44 cm) 2 − 4(44 cm)(11 cm) = 22 cm ....
View Full Document

This note was uploaded on 11/12/2011 for the course PHYS 2001 taught by Professor Sprunger during the Fall '08 term at LSU.

Ask a homework question - tutors are online